Implantable cardioverter-defibrillators in previously undiagnosed patients with catecholaminergic polymorphic ventricular tachycardia resuscitated from sudden cardiac arrest - Werf, Christian van der; Rudic, Boris; Borggrefe, Martin (European heart journal, 2019)
Aims: In patients with catecholaminergic polymorphic ventricular tachycardia (CPVT), implantable cardioverter-defibrillator (ICD) shocks are sometimes ineffective and may even trigger fatal electrical storms. We assessed the efficacy and complications of ICDs placed in patients with CPVT who presented with a sentinel event of sudden cardiac arrest (SCA) while undiagnosed and therefore untreated. Methods and results: We analysed 136 patients who presented with SCA and in whom CPVT was diagnosed subsequently, leading to the initiation of guideline-directed therapy, including β-blockers, flecainide, and/or left cardiac sympathetic denervation. An ICD was implanted in 79 patients (58.1%). The primary outcome of the study was sudden cardiac death (SCD). The secondary outcomes were composite outcomes of SCD, SCA, appropriate ICD shocks, and syncope. After a median follow-up of 4.8 years, SCD had occurred in three patients (3.8%) with an ICD and none of the patients without an ICD (P = 0.1). SCD, SCA, or appropriate ICD shocks occurred in 37 patients (46.8%) with an ICD and 9 patients (15.8%) without an ICD (P < 0.0001). Inappropriate ICD shocks occurred in 19 patients (24.7%) and other device-related complications in 22 patients (28.9%). Conclusion: In previously undiagnosed patients with CPVT who presented with SCA, an ICD was not associated with improved survival. Instead, the ICD was associated with both a high rate of appropriate ICD shocks and inappropriate ICD shocks along with other device-related complications. Strict adherence to guideline-directed therapy without an ICD may provide adequate protection in these patients without all the potential disadvantages of an ICD.